Why is e^-1 the inverse of natural log e? Thank you
Your question is confusing. Let y = ln(x), then x = ey. If x = e, y = 1.
Well I was reading a section on charging/ discharging capacitors and this is what it said: charge on a capacitor builds up on the capacitors plates exponentially, indicated in the passage by the repeated appearance in the charge equation of e^-1, the inverse of the natural log e. And I think the equation they are referring to is Q=Qmax(1- e^-1).
Could it mean "the inverse of the [basis of the] natural log[,] e"? As e-1 = 1/e
Ok I'll go with that because it's what I was thinking too. Thank you!
Separate names with a comma.